DIGITAL TRAPS: "AN ANALYSIS OF THE IMPACT OF ONLINE GAMBLING ON MENTAL HEALTH AND FINANCIAL STABILITY" - Ahmad Fathoni (Dinar : Jurnal Prodi Ekonomi Syariah, 2025)
The phenomenon of online gambling has experienced a significant rise among the Indonesian population, particularly among youth. The "digital traps" factor plays a substantial role in influencing online gambling behavior in Indonesia. First, ease of access: online gambling can be played anytime and anywhere using smartphones or digital devices. Second, the illusion of control: players often feel they have control over game outcomes, although these are purely based on luck. Third, massive advertisements: the frequent promotion of online gambling on social media exacerbates public interest. Online gambling has negative impacts on mental health and financial well-being, making it highly detrimental to the nation's younger generation. This study aims to identify the factors influencing online gambling behavior and analyze its effects on mental health and financial well-being. The research employs a mixed-methods approach, combining quantitative and qualitative research methods. The study design uses a Sequential Exploratory Design and an exploratory research model to understand the phenomenon of online gambling. A mixed-methods approach was implemented with a sample of 400 respondents and interviews with 20 participants. The findings indicate that digital traps (96%), demographics (73.2%), psychological factors (89%), and social influences (94%) significantly affect online gambling behavior. Online gambling also has negative impacts on mental health (stress and anxiety 70%, addiction and dependency 97%, depression 45%, social relationship disorders 20%, sleep disturbances 92%, impulsivity and lack of self-control 87%, productivity decline 24%) and financial well-being (financial losses 95%, mounting debt 75%, financial dependency 70%, asset damage 60%, and difficulty obtaining financial assistance). The study recommends prevention and intervention measures to mitigate the negative impacts of online gambling.